BIOSCAFFOLD FROM MOUSE EMBRYONIC FIBROBLAST MAINTAINS THE PLURIPOTENCY OF MOUSE EMBRYONIC STEM CELLS - Naroeni, Aroem; Novianti, Titta; Jannah, Rifqah Mifthahul (Journal of Stem Cell Research and Tissue Engineering, 2023)
Cell culture using a 3D method provides Various cell culture strategies have been developed using synthetic or biological materials; most existing publications use many reagents. Bioscaffold from mouse embryonic fibroblast (MEF) enhances cell attachment, interaction, and production of growth factors. Since bioscaffolds could maintain and stimulate pluripotency of stem cells, we conducted this study to prove bioscaffold function. Bioscaffold was prepared from MEF cultured in  DMEM complete medium supplemented with dextran sulfate and L-ascorbic acid to increase extracellular matrix production. This medium acts as an embryo stem cell (ESC) culture medium. We used a Tali-cytometer to identify and quantify stem cells based on Sox2 and Oct4 proteins, markers of stemness. ESC culture using bioscaffold maintained the pluripotency of ESC as indicated by the presence of  Oct 4 and Sox2 as ESC markers compared to MEF culture. From this research, the bioscaffold from MEF can be developed as media for ESC to improve propagation. Furthermore, it is a model for tissue engineering and in vitro organ development.